Beyond avian influenza: policy considerations for the implementation of a “one health” approach in developing countries - Okello, Anna Louise (The University of Edinburgh, 2013)
The global One Health movement has become firmly entrenched in both political and scientific discourse pertaining to emerging infectious diseases in the past decade. Since the discovery of the H5N1 strain of Highly Pathogenic Avian Influenza in Hong Kong in 1997, the promotion of more holistic programmes for the control of emerging infectious disease has garnered “unprecedented support” in terms of donor funding and political mobilisation (Scoones 2010). Advocates of One Health argue that intersectoral approaches promoting better communication between the veterinary, medical and environmental disciplines at all levels of governance make not only sound economic sense, they are fundamental to the “new approach” required to address the growing disease threats of the 21st century. However, despite international endorsement of the One Health rhetoric, there is growing pressure to now “turn the rhetoric into reality” (Okello et al 2011). Using a multiple, embedded case study methodology, this thesis seeks to examine questions surrounding the practical implementation of One Health interventions, particularly in developing countries which experience limited resources and competing health priorities. Through examining the livestock and public health policy processes at both local and national levels in Uganda and Nigeria, I attempt to identify whether policy spaces exist for the formal inclusion of One Health approaches in future policy decisions. Furthermore, by scrutinising the current internationally dominant One Health narratives in light of global health governance perspectives and the emerging One Health Global Network, I question whether One Health can be better “packaged” to include endemic diseases and a more focussed sustainable livelihoods approach; arguably inciting greater motivation for developing countries to truly participate. Data from my three empirical chapters are presented in the context of three overriding “One Health propositions” for consideration; by questioning “whose world, whose health”, I aim to delve further into the issues of not whether, but how this “new health paradigm” can be operationalised, and how to address the potential gaps which may ultimately prevent One Health from becoming a truly global phenomenon.
Keywords: avian influenza; Africa; sleeping sickness; One Health; brucellosis